The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/fpc.0b013e32830054ac
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of P450 oxidoreductase: effect of sequence variants on activities of CYP1A2 and CYP2C19

Abstract: The activity of individual POR mutants may vary greatly depending on the electron recipient used to assay activity. Thus, the activity of a POR mutant to support catalysis by a particular P450 enzyme cannot be predicted by the activity of that POR mutant in an assay with a different P450 or with cytochrome c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 51 publications
5
124
1
Order By: Relevance
“…Electron transfer is the rate-limiting step for CYP-catalyzed oxidation-reduction reaction. The POR gene polymorphism (A503V) reduced the activity of CYP17, but had no effect on the activities of CYP1A2 and CYP2C19 (9). The experiments of transgenic mice have demonstrated that decreased activity of POR decreased the enzymatic activity of CYP (10).…”
Section: Introductionmentioning
confidence: 97%
“…Electron transfer is the rate-limiting step for CYP-catalyzed oxidation-reduction reaction. The POR gene polymorphism (A503V) reduced the activity of CYP17, but had no effect on the activities of CYP1A2 and CYP2C19 (9). The experiments of transgenic mice have demonstrated that decreased activity of POR decreased the enzymatic activity of CYP (10).…”
Section: Introductionmentioning
confidence: 97%
“…The majority of these ABS-related POR mutations cause a reduction in CYPOR activity, such as Y181D, involved in FMN binding (Arlt et al, 2004;Huang et al, 2005;Marohnic et al, 2010), Y459H and V492E, involved in FAD binding (Marohnic et al, 2006;Kranendonk et al, 2008), and G539R, positioned in the NADPH binding domain (Huang et al, 2005). Of interest, some mutant proteins such as variant Q153R were reported to support increased P450 activity, compared with the wild-type enzyme (Agrawal et al, 2008Flück et al, 2010;Sandee et al, 2010). Variant A287P has been described as having differential behavior with different P450s (Fukami et al, 2005;Dhir et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of studies on these CYPOR variants were initially focused on steroidogenesis, studies of our group (Kranendonk et al, 2008;Marohnic et al, 2010) and of others (Agrawal et al, 2008;Hart et al, 2008;Gomes et al, 2009) have attempted to evaluate the effects of these CYPOR variants on drug-metabolizing P450s. Two recent studies Flück et al, 2010) described the effect of ABS-related CYPOR variants on the major drug-metabolizing enzyme in humans, CYP3A4, which together with CYP3A5 is estimated to be involved in the metabolism of more than 50% of currently prescribed drugs (Guengerich, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, CYP1A2 and CYP2C19 activities were not supported by Y181D (Agrawal et al, 2008). Shen et al (1989) previously characterized the orthologous Y178D variant of rat liver CYPOR using a bacterially expressed construct.…”
mentioning
confidence: 99%